人―コンピュータ間の社会的インタラクションとその文化依存性―互恵性に基づく対人的反応 - 竹内, 勇剛; 片桐, 恭弘 (Cognitive Studies: Bulletin of the Japanese Cognitive Science Society, 1998)
Human-Computer interaction may be correlated with social interaction and cultural norms. This study explores the validity of the hypothesis that Human-Computer interaction displays the same dynamics as Human-Human interaction. We examined how Japanese and American people respond to a computer as social entity and how cultural differences between Japanese and American behavioral norms in reciprocal social interaction play a role in this response.We first conducted an experiment to test the hypothesis that people interact with a computer as they would with another human. Two groups of subjects experienced positive/negative interaction with a computer which gave them Helpful/Unhelpful tips in completing a Desert Survival task. Subjects were then requested to help either the same computer or a different computer by supplying it with data in a Human Color Perception Task. The results showed that (1) both Japanese and American subjects exhibit behaviors in accordance with social norms of reciprocity, but (2) there is considerable difference between Japanese and American subjects in some conditions, which suggests cultural dependence in people's reaction to computers.In the second experiment, Japanese subjects were tested, after a positive interaction with a computer, in the following three conditions: subjects were requested to provide information to (1) the same benefactor computer, (2) a new computer that belongs to the same group as the first benefactor computer, or (3) a new computer which belongs to a different group from the benefactor computer. The results showed that reciprocal behavior in Japanese subjects is group-oriented, which presumably reflects the cultural characteristics of the Japanese in Human-Human interaction.